O Conselho Municipal de Desenvolvimento Sustentável (CMDS) e a gestão de recursos hídricos: um estudo na Bacia do Rio Itabapoana (RJ) - Faria, Marília de Sant'anna (2005)
The objective of this dissertation is the analysis of the performance of CMDS and its contribution to the management of water resources in the five cities of Rio de Janeiro State, pertaining to Itabapoana river’s basin. This study was lead from a theoretician discussion about local development, citizenship, local development with citizenship and social management. Subsequently, interviews based in the non-probabilistic method was made with a sampling of 38 people among council members of CMDS (members of the government and of organized civil society), technician, consultants and managers from Sebrae/RJ. The data was studied through the analysis of speech. In the evaluation of the performance and the working of the CMDS in the analyzed cities, it was identified negative and positive aspects. Even so, it can be verified that most of the council members have previous experience in Councils and social movements and that the Managé Project, by the performance of the Councils, helped to build a territorial identity to the basin and also aroused to the necessity to make people become aware of and preservation of environment. It can be concluded that, the performance of CMDS depends on the interaction and the level of commitment of public power and organized civil society. Therefore, the local institutional conditions have important influence in the way of the social mobility and participation of the people, considering that the process of the management of water resources of the basin are still in construction process.